2021
DOI: 10.1088/1755-1315/789/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

The Variability of Upper-Ocean Salinity in the Eastern Inflow Region of ITF

Abstract: The north and south Pacific waters influenced the water mass profile in the eastern inflow region of Indonesian throughflow (ITF), including Halmahera Sea, Maluku Sea, and Sangihe–Talaud Waters. Pacific waters are characterized by the strong salinity stratification in the upper-ocean (0–300m depth). Repeated annual oceanographic observations in the eastern inflow region of ITF found anomalous upper-ocean salinity profiles during the 2014–2017 periods. At the end of 2015 (El Niño condition), saltier salinity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A drastic decrease in salinity occurred in the South Halmahera Strait and Obi Strait, remaining the salinity of ~34.6 in the Maluku Sea (Stations 1). Recent studies also indicated that this water masses are the South Pacific Subtropical Water (SPSW) [17], [28], [27]. Even though the characteristic salinity range is not the same as in the area where it was formed, the maximum salinity characteristics are still visible in the Halmahera Sea [29].…”
Section: Typical Watermasses Characteristicmentioning
confidence: 99%
“…A drastic decrease in salinity occurred in the South Halmahera Strait and Obi Strait, remaining the salinity of ~34.6 in the Maluku Sea (Stations 1). Recent studies also indicated that this water masses are the South Pacific Subtropical Water (SPSW) [17], [28], [27]. Even though the characteristic salinity range is not the same as in the area where it was formed, the maximum salinity characteristics are still visible in the Halmahera Sea [29].…”
Section: Typical Watermasses Characteristicmentioning
confidence: 99%